2021
DOI: 10.3390/v13081591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA Interference Pathways in the Insect Vector Laodelphax striatellus by Viral Proteins of Rice Stripe Virus

Abstract: RNA interference (RNAi), especially the small interfering RNA (siRNA) and microRNA (miRNA) pathways, plays an important role in defending against viruses in plants and insects. However, how insect-transmitted phytoviruses regulate the RNAi-mediated antiviral response in vector insects has barely been uncovered. In this study, we explored the interaction between rice stripe virus (RSV) and the miRNA and siRNA pathways of the small brown planthopper, which is a vector insect. The transcript and protein levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The genome of RSV contains four RNA segments and encodes an RNA-dependent RNA polymerase (RdRp), a nucleocapsid protein (NP), and five nonstructural proteins (NS2, NSvc2, NS3, SP, and NSvc4) [ 18 ]. For the coordination between RSV and insect vector immune systems, in addition to inducing apoptosis reactions through binding the transcription factor YY1 in the nuclei of midgut cells and suppressing proteolytic activation of prophenoloxidase in the hemolymph [ 19 ], RSV generates a great number of vsRNAs and directly interacts with RNAi systems [ 14 , 20 ]. Furthermore, we found that one endogenous miRNA, miR-263a, binds the 3’ terminal extension sequence of one genomic RNA of RSV to promote virus replication by eliminating the adverse effect of 3’ extensions on viral promoter activity in small brown planthoppers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genome of RSV contains four RNA segments and encodes an RNA-dependent RNA polymerase (RdRp), a nucleocapsid protein (NP), and five nonstructural proteins (NS2, NSvc2, NS3, SP, and NSvc4) [ 18 ]. For the coordination between RSV and insect vector immune systems, in addition to inducing apoptosis reactions through binding the transcription factor YY1 in the nuclei of midgut cells and suppressing proteolytic activation of prophenoloxidase in the hemolymph [ 19 ], RSV generates a great number of vsRNAs and directly interacts with RNAi systems [ 14 , 20 ]. Furthermore, we found that one endogenous miRNA, miR-263a, binds the 3’ terminal extension sequence of one genomic RNA of RSV to promote virus replication by eliminating the adverse effect of 3’ extensions on viral promoter activity in small brown planthoppers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%